RANGE OF CHILDREN'S OUTDOOR PLAYING AREA IN DENSELY POPULATED AREA TOWARDS SUSTAINABLE CITY - Simanjuntak, Dewi Lestari; Hasibuan, Hayati Sari; Asteria, Donna (Journal of Environmental Science and Sustainable Development, 2022)
Children need to play, either alone or with friends, especially in outdoors spaces, to benefits their growth and development. Many densely populated areas do not provide children's playgrounds due to the limited area and not planned from the start of development. As a result, children play in the remaining space around the residence, which can threaten the safety and comfort of children. It is essential to pay attention to the safety and comfort aspects of children. This paper aims to explain the spatial reach of children when playing outdoors and children's perceptions about their playing area. This research was conducted in Keluranan Kalianyar every day from Monday to Sunday, in the morning and afternoon. Conducted interviews with 347 children accompanied by one of their parents and studied literature. The study found that most of the children playing near home (about less than 40 meters and 40-100 meters from their home). Second, 64% of children believe that playing space is unsafe, and 69% believe that playing space is uncomfortable for all children. This study explains that although no play area meets the elements of safety and comfort, children can still play at a distance that is still affordable from their home. Thus, efforts are needed to enhance the safety and comfort of children's play spaces.